The Effect of Rate of Money Supply (M2), Interest Rates and Exchange Rates on the Composite Stock Price Index (JCI) - Handreana Rheymanda Setiawan; Moh Yudi Mahadianto; Mardi Mardi (Asian Journal of Management Analytics, 2026)
This study analyzes the influence of the Rate of Money Supply (M2), BI interest rates, and exchange rates on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange for the 2020–2024 period. Applying a descriptive quantitative approach through multiple linear regression analysis, this study processes secondary data in the form of 60 monthly observations obtained from the official websites of the Central Statistics Agency (BPS) and the Indonesia Stock Exchange (IDX). The results of the partial test (t-test) indicate that the rate of money supply (M2) and interest rates have a positive and significant effect on the JCI, indicating that increased economic liquidity can encourage investment activity in the capital market. In contrast, the Rupiah exchange rate has a negative and significant effect on the JCI, where exchange rate depreciation tends to suppress stock market performance.